PENGARUH PANJANG DAN KESEJAJARAN ANTARA LANTAI INJAK DENGAN LANTAI JEMBATAN DI AWAL BENTANG TERHADAP TINGKAT KERUSAKAN LANTAI JEMBATAN - Andi Indianto; Setiyadi Setiyadi (Politeknik Negeri Jakarta, 2018)
ABSTRACTThis research presenting the influence of the length and extent of the approach floor on the oprit against damage to the bridge deck. This research is done because most of the damage to the bridge deck occurred at the beginning of the span.The purpose of this research is to know how big influence of length and alignment of approach floor to damage of bridge floor at beginning of span.To achieve the above purpose,conducted research against 18 bridges in Depok and Cibinong. With sampling in the form of long approach floor, alignment of the floor stepped on the bridge deck at the beginning of the span, observation of bridge deck damage and width measurement cracked the bridge deck at the beginning of the span. After the data has been collected, the next step is to analyze the effect of floor length and alignment on the bridge deck damage. The results show that length and alignment approach floor with a bridge deck the beginning of the span is very influential on damage to the bridge deck at the beginning of the span, with a confidence level of 0.77. The bigger the slope difference of the approach floor with the slope of the bridge deck at the beginning of the span, and getting shorter approach floor damage to the bridge deck at the beginning of the span is getting bigger.Keywords: Approach floor, bridge deck.